Pengaruh Kompetensi, Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai - Daud, Ismet; Lamuda, Ilyas; Suyanto, Moh. Affan; Paramata, Moh. Rolli; Karundeng, Deby Rita (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study aims to determine the influence of competence, work environment, and work motivation on the performance of employees at the Office of Labor, Cooperatives, and SMEs in Gorontalo City. The data analysis methods used include Descriptive Statistical Test, Classical Assumption Test, Hypothesis Test, and Multiple Linear Analysis. The results of this study indicate that, based on the t-test results for the competence variable (X1) on employee performance (Y), the significance value is 0.037. It can be concluded that competence has a positive and significant effect on employee performance. The t-test results for the work environment variable (X2) on employee performance (Y) show a significance value of 0.027. It can be concluded that the work environment has a positive and significant effect on employee performance. The t-test results for the work motivation variable (X3) on performance (Y) show a significance value of 0.032. It can be concluded that work motivation has a positive and significant effect on employee performance. The simultaneous test of the influence of competence (X1), work environment (X2), and work motivation (X3) on employee performance (Y) shows an F calculated value of 4.673, which is greater than the F table value of 2.960, and a significance value of 0.009, which is less than the probability value of 0.05. This means that simultaneously, competence (X1), work environment (X2), and work motivation (X3) have a significant effect on employee performance.